Improving yam production in Benin: Variety and quality concerns - Honfozo, Laurenda; Pede, Pénélope; Adinsi, Laurent; Hotegni, Francis; Anihouvi, Eudes; Tran, Thierry; Dufour, Dominique; Mbéguié-A-Mbéguié, Didier; Akissoe, Noël (CGIAR Science Program on Breeding for Tomorrow, 2025)
Yam (Dioscorea sp.) is a staple food and plays a crucial role in food security across West Africa. It is widely consumed in both rural and urban areas. However, significant challenges threaten, such as declining yields, seed rot, soil fertility loss, as well as climate change. In response, various agricultural research institutions and farmers have adopted strategies to ensure year-round availability of high-quality yam and promote good agricultural practices.